1999
DOI: 10.1016/s0924-9338(99)80735-4
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography study of pineal calcification in schizophrenia

Abstract: Computed tomography studies concerning pineal calcification (PC) in schizophrenia have been conducted mainly by one author who correlated this calcification with several aspects of the illness. On the basis of these findings the aim of the present study was to analyze size and incidence of pineal gland calcification by CT in schizophrenics and healthy controls, and to verify the relationship between pineal calcification and age, and the possible correlation with psychopathologic variables. Pineal calcification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…However, change in positive TD, as well as change in negative TD and negative TD at follow-up, each failed to correlate significantly with the percentage change in pituitary volume over time. Bersani et al (1999b) found that those with more severe positive TD had smaller pineal gland calcification lengths, though negative TD did not show the same correspondence. Conversely, Sandyk (1993b), who conducted the only TDmotivated study of the neuroendocrine system, found that individuals with more severe positive TD had greater pineal calcification than those with milder manifestations.…”
Section: Neuroendocrine System (Pituitary and Pineal Glands)mentioning
confidence: 80%
“…However, change in positive TD, as well as change in negative TD and negative TD at follow-up, each failed to correlate significantly with the percentage change in pituitary volume over time. Bersani et al (1999b) found that those with more severe positive TD had smaller pineal gland calcification lengths, though negative TD did not show the same correspondence. Conversely, Sandyk (1993b), who conducted the only TDmotivated study of the neuroendocrine system, found that individuals with more severe positive TD had greater pineal calcification than those with milder manifestations.…”
Section: Neuroendocrine System (Pituitary and Pineal Glands)mentioning
confidence: 80%
“…Several lines of evidence suggest a possible relationship between pineal gland abnormalities and symptoms of thought disorder. In particular, pineal gland irregularities (e.g., calcification) have been observed in patients with schizophrenia (13), and others have noted that these abnormalities may be related to abnormal nocturnal melatonin secretion in patients with schizophrenia (14). Anecdotal reports have also suggested that high doses of melatonin may exacerbate psychotic symptoms in patients with schizophrenia (15).…”
Section: Discussionmentioning
confidence: 99%
“…(1998) also found a larger area of epithalamus calcification in schizophrenics compared to control subjects. That this may be mainly due to increased calcification of habenula, rather than of the pineal, is suggested by observations of no difference in size of pineal calcification in schizophrenics (Bersani et al ., 1999). Based on several findings, particularly the fact that chronic treatment with cocaine or amphetamine severely damages the fasciculus retroflexus output pathway of the habenula in rats and results in a schizophrenia‐like state in man, Ellison (1994) has proposed a role for habenula pathology in schizophrenia.…”
Section: Introductionmentioning
confidence: 90%